THE POSITIVE AND NEGATIVE EFFECT OF SOCIAL MEDIA ON THE YOUTH’S STATE AND NATION DEVELOPMENT - Suhendar Suhendar (STIBA IEC JAKARTA, 2018)
Social media mostly provides facilities and applications which make the youth enjoy their time longer in using social media. In relation to which, the objectives of this study are to identify what are the positives and negatives effects of social media on the youth’s state and nation development. As for the method used herein is qualitative in nature and the method of collecting data applied herein is by adopting literary approach. Positive impact of social media are among the other things: to keep in touch with the members of family living so far from house or with the relative which have not met for a long time; to use it as teaching and learning sources; to use it as information media; to broaden fraternity networks; to use it as the facility to improve skill and competence; to use it as communication media; and to use it as promotion and business media. Meanwhile negative effect of social media are among the other things are: difficult to socialize with the people surrounding; social media can make somebody only think about him/herself; the lack of working performance; criminal in cyberspace; and pornography. Accordingly, by knowing positive and negative impact of social media the youth can be wiser to use it only for the purpose of developing the state and nation.